Perancangan Alat Press Hidrolik Kapasitas 20 Ton - Amsal, Amsal; Afdal, Afdal; Zulkarnain, Zulkarnain; Abu, Risal; Mukhnizar, Mukhnizar (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
A press tool is a tool to help shape, bend, cut products from sheet metal (plate) base material which is operated using a press tool. To increase effectiveness and productivity, currently many hydraulic systems are combined with other systems such as electrical/electronic, pneumatic and mechanical systems so that more optimal hydraulic system work can be obtained. This press applies pressing or loading movements using hydraulic power. In order for the pressing process to be even or precise, one cylinder is needed which moves the top plate (Punch). The working load on the single acting cylinder has a maximum capacity of 20 tons. The design of this press tool is designed by following the type and shape of the selected material sample. The design of this press tool aims to make the user's work easier to get more precise press results. The material used is profile steel. Simulation results on the press frame: frame length 400 mm, frame width 600 mm, frame height 850 mm, frame strength 16407 N/m2